1988
DOI: 10.3109/02699058809150949
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of self report among non-oriented head-injured adults

Abstract: Two groups of head injury clients (oriented and non-oriented) and a group of non-disabled participants were compared on response consistency to a MMPI test. Over three testing sessions it was found that the non-oriented head injury group had the most inconsistent responses followed by the oriented head injury group and the control group. Though six of the 21 MMPI profiles from the non-oriented clients were identified as invalid, MMPI validity scales did not effectively detect unreliable responders. Results sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
1998
1998

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Only persons with GOAT scores of at least 80 or above were included in the study. Priddy, Mattes, and Lam (1988) found that nonoriented persons with TBI (those with scores of less than 80 on the GOAT) were less able to accurately self-report than oriented persons with TBI (those with GOAT scores of 80 or higher).…”
Section: Methods Participantsmentioning
confidence: 91%
“…Only persons with GOAT scores of at least 80 or above were included in the study. Priddy, Mattes, and Lam (1988) found that nonoriented persons with TBI (those with scores of less than 80 on the GOAT) were less able to accurately self-report than oriented persons with TBI (those with GOAT scores of 80 or higher).…”
Section: Methods Participantsmentioning
confidence: 91%
“…All methods of measuring awareness that use patient selfratings depend on patients having some capacity to reliably rate their abilities even though such ratings are likely to be overestimates. Clearly, such an assumption is not warranted for nonresponsive or acutely confused patients (Priddy et al, 1988). However, there is evidence that some oriented patients may be too cognitively impaired to produce meaningful self-ratings (Boake et al, 1995).…”
Section: Measurement Of Impaired Awarenessmentioning
confidence: 99%